Integrating distributed generator for restoration optimization - Abu Hanifah, Mohd Shahrin; Nosu, Kiyoushi; Hidenori, Aoki (IEEE, 2013)
Restoration Service has become important as distribution systems are becoming automated. However, because it is a complex control problem involves heuristic searches, there is still hard to find optimal solution. On the other hand, in recent years, Distributed Generators (DG) is being actively introduced in distribution systems. This paper proposed the integration of enhanced efficiency and environmental friendliness usage of heat and power, low emissions and noise of DG as a method for restoration optimization and the simulation result are showed.